Sheltering difference: (un)doing the migrant/volunteer divide through sheltering practices in Mexico and the Netherlands - Merlín-Escorza, Cesar E.; Schapendonk, Joris; Davids, Tine (Frontiers in Sociology, 2023)
While acknowledging the important role of shelter organizations in protecting migrant rights, recent debates point to the thin line between care and control practices within shelters. This study seeks to deepen this observation by approaching shelters as spaces defined by a constant inward/outward mobility of people. From this starting point, we use the de-migranticization framework to understand and question the normalization of difference that divides migrant people (being reproduced as the typical guest) from international volunteers (being reproduced as the typical host) through sheltering practices in two rather different geopolitical contexts (Mexico and the Netherlands). We use our ethnographic insights to not only illustrate how difference is reproduced but also to analyze the practices that seek to transgress and undo these divides. We argue that highlighting the conviviality and interconnectedness between these differentiated actors in the broader context of cross-border mobility is of vital importance to question and overcome the coloniality of contemporary border regimes. However, we do not imply that these aspects have the potential to completely undo difference, as they are a constant struggle embedded in the relational practices of the people composing such a divide.